The Diagnostic Value of Metagenomic Next–Generation Sequencing in Lower Respiratory Tract Infection - Zheng, Yan; Qiu, Xiaojian; Wang, Ting; Zhang, Jie (Frontiers in Cellular and Infection Microbiology, 2021)
Lower respiratory tract infections are associated with high morbidity and mortality and significant clinical harm. Due to the limited ability of traditional pathogen detection methods, anti-infective therapy is mostly empirical. Therefore, it is difficult to adopt targeted drug therapy. In recent years, metagenomic next-generation sequencing (mNGS) technology has provided a promising means for pathogen-specific diagnosis and updated the diagnostic strategy for lower respiratory tract infections. This article reviews the diagnostic value of mNGS for lower respiratory tract infections, the impact of different sampling methods on the detection efficiency of mNGS, and current technical difficulties in the clinical application of mNGS.